Ancestral polymorphisms explain the role of chromosomal inversions in speciation. - Zachary L Fuller; Christopher J Leonard; Randee E Young; Stephen W Schaeffer; Nitin Phadnis (PLoS Genetics, 2018)
Understanding the role of chromosomal inversions in speciation is a fundamental problem in evolutionary genetics. Here, we perform a comprehensive reconstruction of the evolutionary histories of the chromosomal inversions in Drosophila persimilis and D. pseudoobscura. We provide a solution to the puzzling origins of the selfish Sex-Ratio arrangement in D. persimilis and uncover surprising patterns of phylogenetic discordance on this chromosome. These patterns show that, contrary to widely held views, all fixed chromosomal inversions between D. persimilis and D. pseudoobscura were already present in their ancestral population long before the species split. Our results suggest that patterns of higher genomic divergence and an association of reproductive isolation genes with chromosomal inversions may be a direct consequence of incomplete lineage sorting of ancestral polymorphisms. These findings force a reconsideration of the role of chromosomal inversions in speciation, not as protectors of existing hybrid incompatibilities, but as fertile grounds for their formation.